Facile synthesis and self-assembly behaviour of pH-responsive degradable polyacetal dendrimers. Issue 40 (22nd September 2016) - Huang, Da; Yang, Fei; Wang, Xing; Shen, Hong; You, Yezi; Wu, Decheng
Abstract : Well-defined POSS hybrid polyacetal dendrimers functionalized with terminal polyethylene glycol and zwitterion could assemble into pH-responsive degradable micelles and nanofibers. Abstract : Herein, we report the facile synthesis of a class of well-defined acid-labile polyacetal dendrimers, which can be easily functionalized by poly(ethylene glycol) or zwitterions and self-assemble into pH-responsive degradable micelles or nanofibers.